Initiation Time and Time Needed to Achieved Ideal Nutrition Level in Mechanically Ventilated Patient admitted to Intensive Care Unit of Dr. Hasan Sadikin Hospital Bandung - Irawati, Dian; , Suwarman; Redjeki, Ike Sri (Majalah Anestesia dan Critical Care, 2015)
Enteral nutrition need to be given in first 24–48 hour after the patient admitted to the ICU, while ideal nutritional level need to be achieved in 48–72 hours after the patient admitted. Both time are “window opportunity” which influence morbidity and mortality. The aim of this study was to identify the initiation time and the time needed for ideal nutrition achieved in patient with mechanical ventilation. This prospective descriptive-observational study was done from June until September 2015 in ICU of Dr. Hasan Sadikin hospital to 39 subject. Result showed initiation time in 38 subject was done in ≤24 hour. In 24 subject, ideal nutrition level was achieved in more than 72 hour. Reason for delay in initiation rescusitation. Reason for ideal nutrition not fullfiled in less 72 hour was gradual nutrition procedure, intolerance, hemodinamic disturbance, absence of small bowel sound, and high glucose level. In conclusion the intiation time of enteral nutrition in almost all patient of Dr. Hasan Sadikin Hospital from June until September 2015 was done in less than 48 hour. After 72 hour of observation, 58,87% subject cannot achieved ideal nutrition in less than 72 hour.